Pemberdayaan Peternak Kambing Peranakan Etawa (PE) Melalui Sistem Pertanian Terintegrasi Di Desa Genggelang, Kecamatan Gangga, Kabupaten Lombok Utara, Provinsi NTB - Yusuf, M; Nursan, Muhammad; Mandalika, Eka Nurminda Dewi; Septiadi, Dudi (Jurnal Pengabdian Magister Pendidikan IPA, 2024)
In general, the community service activities aim to: increase the knowledge and skills of the community by developing the Etawa cross goat breeding business through an integrated farming system, while in particular this activity aims : (1) Develop interest and motivate the community of Genggelang Village, Gangga. District, North Lombok Regency for entrepreneurship in the fields of agriculture and livestock, especially Etawa cross goat (PE) breeding; (2) Demonstrate to farmers/breeders the technological aspects of Etawa crossbred (PE) goat breeding business that are good and correct; (3) Etawa crossbred (PE) goat farmers can understand the socio-economic aspects (sustainable increase in income); and (4) Establish relationships between universities, especially Mataram University, and the community. This community service uses community development methods that emphasize adult learning, involving 8 members of the target group. Overall, the implementation went well and smoothly, as indicated by the active participation of the target group and the acceptance of the science and technology offered by the target group; In particular, this community service activity has been able to increase the knowledge and skills of the participants, especially those related to: (1) Increasing the knowledge and skills of Etawa cross-bred (PE) goat farmers regarding aspects of cultivation techniques integrated with food crops. in supporting the family economy; (2) Increase group members' awareness of the importance of togetherness in a group bond; (3) Increased knowledge and management skills of members of the Etawa cross goat breeders (PE) group in an effort to utilize the existing potential and create mutually beneficial cooperative relationships between the group, universities and local governments, especially the existing Etawa crossbred (PE) goats. breeders in Genggelang Village, Gangga District, North Lombok Regency;